Sistem Informasi Registrasi Pasien dan Rekam Medis pada Rumah Sakit Umum Daerah Waibakul (RSUD) Kabupaten Sumba Tengah Berbasis Web - Frikles Pahangara; Adelbertus Umbu Jangga; Maria Wilda Malo (Pusat Riset dan Inovasi Nasional, 2025)
Simplifying the process of administering medical records and patient registration in hospitals is the goal of the web-based Patient Registration and Medical Record Information System at the Waibakul Regional General Hospital (RSUD) in Central Sumba Regency. In the past, manual patient registration often resulted in long waiting times, inaccurate data entry, and difficulty in finding patient information. This web-based solution speeds up the process of searching for patient medical information, coordinating patient data management for hospital staff, and enabling online patient registration. This system is built using web technology that allows flexible access and works with a variety of devices, including PCs and smartphones. The main features developed are electronic medical record management, fast and accurate patient data search, recording of health history, and registration of new patients. In addition, this system has data that may help hospitals make better and more efficient decisions. The test results show that this system can reduce the possibility of data errors, speed up patient registration procedures and maintenance of medical records, and improve the quality of health services provided at RSUD Waibakul. Therefore, this information system is expected to facilitate the acquisition of health information by patients and medical personnel and help improve hospital administration.